SUPPLY CHAIN STRATEGY IN INITIAL PUBLIC OFFERING IN MALAYSIA: A REVIEW OF LONG-RUN SHARE PRICE PERFORMANCE - Abdullah, Yasir; Ahmad-Zaluki, Nurwati A.; Abd Rahim, Nazahah (International Journal of Supply Chain Management, 2019)
Abstract- The paper examined the current status of research regarding the long-run share price performance of initial public offerings (IPO) in Malaysia. The review on previous â??studies was divided into the followings: underwriter reputation, earnings management, and board variablesâ??. The paper found that â??there was a noticeable poor long-run performance, and Malaysian IPOs were lesser than others from developed nations. The evidences of the long-run performance were inconsistent. This paper pinpointed significant factors that could â??influence the â??â??long-run share price performance in the Malaysian IPO market. New areas for future research were also suggested.